Age-related trends in the trabecular micro-architecture of the medial clavicle: Is it of use in forensic science? - McGivern, Hannah; Greenwood, Charlene; Márquez-Grant, Nicholas; Kranioti, Elena F.; Zioupos, Peter (Cranfield University, 2020)
The mechanical and structural properties of bone are known to change significantly with age. Within forensic and archaeological investigations, the medial end of the clavicle is typically used for estimating the age-at-death of an unknown individual. Although, this region of the skeleton is of interest to forensic and clinical domains, alterations beyond the macro-scale have not been fully explored. For this study, non-destructive micro-computed tomography (µ-CT) was employed to characterise structural alterations to the cancellous bone of the medial clavicle. Fresh human cadaveric specimens (12-59 years) obtained at autopsy were utilised for this study, and were scanned with a voxel size of ~83µm. Morphometric properties were quantified and indicated that the bone volume, connectivity, mineral density and number of trabeculae decreased with age, while the spacing between the trabeculae increased with age. In contrast to other sub-regions of the skeleton, trabecular thickness and degree of anisotropy did not correlate with age, which could suggest that the network is becoming increasing perforated with age rather than exhibiting trabecular thinning. These results are used in the context of deriving a potential protocol for forensic investigations by using this particular and largely unexplored region of the skeleton and provide inspiration for future experiments concerning micro-architectural and small scale changes in other regions of the human skeleton.
Keywords: 'Clavicle'; 'Cancellous bone'; 'Ageing'; 'Micro-computed tomography'; 'Forensic Science'; 'Biomechanics'; 'Forensic Biology'